Prevalence and Factors Associated with Disclosure of HIV Diagnosis to Infected Children Receiving Antiretroviral Treatment in Public Health Care Facilities in Gauteng, South Africa - Sphiwe Madiba; Johanna Mahloko; Kebogile Mokwena (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
HIV infected children who started antiretroviral therapy (ART) in public health facilities in South Africa have survived to older age and disclosure has become an essential part of their care. Available data on HIV disclosure to children were collected much earlier in the provision of ART in South Africa. The aim of the study was to (a) determine the characteristics of caregivers of pediatric HIV patients in Gauteng, South Africa, (b) estimate the prevalence and timing of HIV disclosure among these patients, and (c) assess the factors associated with disclosure status. A cross-sectional study was conducted among 286 caregivers of paediatric ART children aged 4–17 in two centres in Gauteng, South Africa. Bivariate and multivariate logistic regression analyses were carried out. The highest proportion of care givers were biological mothers (n=140, 49.3%). The mean age of the children was 8.5 years, (range 4-17 years). More than a third (n=99, 34%) were disclosed their HIV status, and the mean age at disclosure was 9.3 years, (SD = 2.7). Child’s age older than 10 years (OR =1.63; 95% CI: 1.44–1.85), having a nonbiological caregiver (OR=1.75; 95% CI: 1.06-2.89), caregiver educational level (OR =0.64; 95% CI: 0.47–0.87), and caregiver’s age older than 60 years (OR=1.02; 95% CI: 1.01-1.04), were significantly associated with HIV disclosure to infected children. The relatively higher prevalence of disclosure is attributed to increasing access to paediatric ART. Training healthcare providers to support caregivers in disclosure will increase the rate of disclosure to HIV infected children receiving ART in public health facilities.
Keywords: Disclosure